2007
DOI: 10.1111/j.1444-0938.2007.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some factors affecting the agreement between the Proview Eye Pressure Monitor and the Goldmann applanation tonometer measurements

Abstract: Background:  Our aim was to examine whether training level and ocular factors could account for part of the difference in intraocular pressure (IOP) measured using the Goldmann applanation tonometer (GAT) and Proview Eye Pressure Monitor (PPT). Methods:  One hundred and nineteen individuals (238 eyes) were enrolled in the study. The mean age was 35.8 years (range 21 to 79). All study participants obtained IOP measurements using the PPT after hearing instructions on how to perform PPT. Glaucoma patients obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In total, 10 studies 124,127,137,138,168,176,178,191,198,208 (50%) reported individual measures taken within 1 hour. In 12 studies (60%) the same clinical data were available for interpretation as would be available in clinical practice 124,127,133,137,138,158,162,168,172,177,205,207 and it was reported that the examiner(s) were masked to the results. 124,125,158,162,168,172,[176][177][178]205,207,208 In seven studies 125,127,172,177,178,205,208 (35%) the tonometers used were calibrated.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 10 studies 124,127,137,138,168,176,178,191,198,208 (50%) reported individual measures taken within 1 hour. In 12 studies (60%) the same clinical data were available for interpretation as would be available in clinical practice 124,127,133,137,138,158,162,168,172,177,205,207 and it was reported that the examiner(s) were masked to the results. 124,125,158,162,168,172,[176][177][178]205,207,208 In seven studies 125,127,172,177,178,205,208 (35%) the tonometers used were calibrated.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
“…In the Tai and colleagues study 125 the mean IOP difference between the phosphene tonometer and GAT was 4.3 mmHg for patients with the lowest IOP (< 10 mmHg), 0.4 mmHg for patients with IOP within the normal range (10-20 mmHg), -2.7 mmHg for patients with higher IOP (20-30mmHg) and -6.1 mmHg for patients with severe OHT (IOP > 30 mmHg). Gunvant and colleagues 133 carried out a similar subgroup analysis of mean IOP difference by categorising patients as either healthy or glaucomatous, but this is not directly equivalent to an IOP subgroup analysis. Only two 133,138 studies reported CCT results, both of which presented results in relation to the IOP difference between GAT and transpalpebral tonometry.…”
Section: Clinical Factor Analysesmentioning
confidence: 99%
See 3 more Smart Citations